A Study on Effect of Globalization on Changing Food Patterns among Students - masoumeh bagheri; karim rezadousat; mahmoud avini; elaheh mavalizadeh (توسعه اجتماعی)
Globalization is a process which unit all the people around the world. The purpose of this study was to investigate the effect of globalization on changing the food patterns among students. Data was collected from 385 student selected through stratify random sampling method. The researcher made questionnaire consist in of liker type questions. Finding showed that globalization has significant effect on changing the food pattern among students. Thus the independent variables such as internet, propaganda, fashion's, peer groups had the most influence on changing the food patterns of students.